First and Second Timothy, Titus, Philemon - Keegan, Terence J. (Collegeville, Minn. : Liturgical Press, 2006)
"Complete biblical texts with sound, scholarly based commentary that is written at a pastoral level; the Scripture translation is that of the New American Bible with Revised New Testament and Revised Psalms (1991)"--Provided by publisher.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries